1985
DOI: 10.1051/rnd:19850801
|View full text |Cite
|
Sign up to set email alerts
|

Plasma catecholamine concentrations in lambs and calves during the perinatal period

Abstract: Summary. Concentrations of the plasma catecholamines (CA), adrenaline, noradrenaline and dopamine, were measured using a specific and sensitive radioenzymatic assay in 7 ewes and their single lambs chronically catheterized in utero between days 127 and 145 of gestation and during the first week of postnatal life. These concentrations were also measured during the first month after birth in 18 Holstein x Friesian calves, of which 9 were born spontaneously at term (278 days) and 9 by caesarean section on day 260… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…This leads to a big reduction of the insulin/glucagon molar ratio and favors catabolic processes that lead to glycogen mobilization, starting at the second postnatal hour [34,35]. As previously mentioned glycogen mobilization is provoked mainly by catecholamine increase supported by a decreased insulin/ glucagon molar ratio.…”
Section: Insulin and Glucagonmentioning
confidence: 83%
See 1 more Smart Citation
“…This leads to a big reduction of the insulin/glucagon molar ratio and favors catabolic processes that lead to glycogen mobilization, starting at the second postnatal hour [34,35]. As previously mentioned glycogen mobilization is provoked mainly by catecholamine increase supported by a decreased insulin/ glucagon molar ratio.…”
Section: Insulin and Glucagonmentioning
confidence: 83%
“…Although plasma catecholamine concentrations are very high at delivery a rapid decrease during the fi rst 30 minutes of postnatal life is found, followed by a signifi cant increase in their concentrations at the second postnatal hour, which coincides with the highest cAMP concentrations observed in the liver and with the onset of signifi cant liver glycogen mobilization [34,35]. The occurrence of postnatal hypoglycemia could stimulate the increase in plasma catecholamine concentrations in the second postnatal hour.…”
Section: Cathecholaminesmentioning
confidence: 96%
“…Besides glucagon and cortisol, catecholamines are involved in eGP and stimulate hepatic glycogenolysis and GNG through α 1and β 2 -adrenergic receptors (Rizza et al, 1980;Kraus-Friedmann, 1984), also shown in ruminants (McDowell, 1983;Brockman and Laarveld, 1986) and neonatal calves (Carron et al, 2005b;Hammon et al, 2012). In addition, catecholamines play an important role in postnatal glucose homeostasis (Sperling et al, 1984) and plasma concentrations of catecholamines are elevated around birth (Richet et al, 1985;Fowden et al, 1998). Whether plasma catecholamine concentrations are affected by nutrition in neonatal calves, is presently not known.…”
Section: Dependence Of Endocrine Glucose Regulation On Colostrum Supplymentioning
confidence: 99%
“…Plasma concentrations of adrenaline and noradrenaline are elevated around birth and support metabolic adaptation for postnatal life (Eliot et al, 1981;Richet et al, 1985;Hume et al, 2005). Effects of adrenaline and noradrenaline are mediated by α-and β-AR, respectively, which are present in liver cell membranes (Rizza et al, 1980;Schmelck and Hanoune, 1980).…”
mentioning
confidence: 99%